2018
DOI: 10.1111/gcb.14110
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of global land use and management intensity to changes in climate and atmospheric carbon dioxide

Abstract: Land use contributes to environmental change, but is also influenced by such changes. Climate and atmospheric carbon dioxide (CO 2) levels’ changes alter agricultural crop productivity, plant water requirements and irrigation water availability. The global food system needs to respond and adapt to these changes, for example, by altering agricultural practices, including the crop types or intensity of management, or shifting cultivated areas within and between countries. As impacts and associated adaptation res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 99 publications
(159 reference statements)
0
53
0
Order By: Relevance
“…GGCs assess crop productivity as well as agricultural water and fertilizer requirements based on a combination of the biophysical properties (e.g., soil, climate) and human-driven management decisions (e.g., water interventions, fertilization, crop choice). However, these models do not typically have an explicit economic component and thus cannot optimize management responses to changes in climate and food demands [33,34]. Rather, they estimate static productivity impacts under pre-specified management regimes or, alternatively, the resource requirements required to alleviate gridded resource constraints (e.g., the fertilizer and irrigation required to avoid nitrogen and water stress, respectively).…”
Section: Land Productivity and The Influence Of Climate And Water Conmentioning
confidence: 99%
“…GGCs assess crop productivity as well as agricultural water and fertilizer requirements based on a combination of the biophysical properties (e.g., soil, climate) and human-driven management decisions (e.g., water interventions, fertilization, crop choice). However, these models do not typically have an explicit economic component and thus cannot optimize management responses to changes in climate and food demands [33,34]. Rather, they estimate static productivity impacts under pre-specified management regimes or, alternatively, the resource requirements required to alleviate gridded resource constraints (e.g., the fertilizer and irrigation required to avoid nitrogen and water stress, respectively).…”
Section: Land Productivity and The Influence Of Climate And Water Conmentioning
confidence: 99%
“…future are discussed in Alexander et al (2018). Here, after extending the historical run to 2010, we feed PLUM's projections of 2011-2100 land use, nitrogen fertilizer application, and irrigation intensity back into LPJ-GUESS to simulate their impacts over that period.…”
Section: Lpj-guess and Ecosystem Servicesmentioning
confidence: 99%
“…In addition to the input data provided by the SSPs, and following the approach described in Alexander et al (2018), PLUM parameters-such as input and transport costs, tariffs, and minimum non-agricultural area-were also affected by the SSP narratives. Values were estimated for each SSP based on an interpretation of the storylines (O'Neill et al, 2015;Engström et al, 2016a) and can be found in Table SM6.…”
Section: Input Data: Plummentioning
confidence: 99%
See 2 more Smart Citations